Acute Toxicity Test of Pineapple Peel Aqueous Extract (Ananas comosus L.) With BSLT Method - Fardiaz, Muhammad Abdurrahman; Pratama, Iman Surya; Aini, Siti Rahmatul (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Pineapple peel waste can be processed into pharmaceutical dosage form, but research related to the toxicity of pineapple peel is  still limited. Based on the LC50 value and the description of morphological damage in Artemia salina larvae, this study seeks to establish the acute toxicity of pineapple peel aqueous extract. The method used is the Brine Shrimp Lethality Test (BSLT). Preliminary tests were carried out using each of 10 Artemia salina larvae in 10 mL of pineapple peel water extract at concentrations of 10000;1000;100;10;1; 0.1 ppm. Based on the results of the preliminary test, the definitive test was conducted with seven concentration variations, plus a saltwater negative control and a potassium dichromate 39.06 ppm positive control. After 24 hours, observations were performed on the number of deaths and morphological damage of Artemia salina larvae. An LC50 value will be generated by performing a probit analysis on data regarding the number of larvae deaths using Microsoft Excel. A morphological damage of Artemia salina larvae were analyzed descriptively. Results of the preliminary test are presented as concentration ranges for the final test, including 100, 251, 630, 1583, 3975, 6987, and 10,000 ppm. The LC50 value obtained based on the definitive test was 1185 ppm. Morphological damage to Artemia salina larvae due to exposure to water extract of pineapple peel occurred in the antenula, appendages, abdomen, and digestive tract. Pineapple peel water extract belongs to the non-toxic category with LC50 value is > 1000 ppm. Morphological damage to Artemia salina larvae occurred at concentrations of 630-10000 ppm.